Design and implementation of a data pick up system in apparel industry - Ferreira, Tânia (2020)
The layout of the factories in the apparel industry has several processing stations that are grouped in sections that have to do with a particular task (ex. trousers stitch). This together with high levels of production capacity demands the implementation of automatic monitoring systems that allow some sort of feedback related with the production progress of those stations. This paper describes a system that is being developed at Escola Superior de Tecnologia de Castelo Branco, which is part of the Instituto Politécnico de Castelo Branco. It consists of a prototype for a real time data pick up system, using the Controller Area Network (CAN) [1] bus. The aimed objective is to collect the data contained in bar code labels that are coupled to cloths pieces in an apparel factory during the production process. Those labels have useful information to the production stage (ID number of the piece), and accompany each apparel piece. This system is part of a more global system that will allow the production management using a wed platform linking the commercial, production scheduling, manufacturing control and customer/seller stages.